2023
DOI: 10.1093/biosci/biad012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that behavioral nudges in citizen science projects can improve biodiversity data

Abstract: One way to improve the value of citizen science data for a specific aim is through promoting adaptive sampling, where the marginal value of a citizen science observation is dependent on existing data collected to address a specific question. Adaptive sampling could increase sampling at places or times—using a dynamic and updateable framework—where data are expected to be most informative for a given ecological question or conservation goal. We used an experimental approach to test whether the participants in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Our results show that adaptive sampling improved the performance of SDMs, even at low levels of uptake. This supports the proposition that optimising data collection by citizen scientists could be a powerful mechanism to maximise the potential of these datasets (Callaghan et al, 2023;Kays et al, 2021;Xue et al, 2016).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Our results show that adaptive sampling improved the performance of SDMs, even at low levels of uptake. This supports the proposition that optimising data collection by citizen scientists could be a powerful mechanism to maximise the potential of these datasets (Callaghan et al, 2023;Kays et al, 2021;Xue et al, 2016).…”
Section: Discussionsupporting
confidence: 70%
“…For example, many schemes try to maintain the same sampling design because they are interested in trends through time, as well as increasing spatial coverage of their data. We, and others, have shown that adaptive sampling can work for improving estimates of species' distributions (Callaghan et al, 2023;Camp et al, 2020;Kays et al, 2021;Shanahan et al, 2021) and trend detection Lindenmayer & Likens, 2009). However, further work needs to consider trade-offs between the intended and unintended outcomes of adaptive designs.…”
Section: Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crinia sloanei in the Albury area of NSW by the Sloane’s Champions: Rowley et al . 2019) and communicating spatial and temporal priorities to participants could be used to further optimise data collection (Callaghan et al . 2023; Thompson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Technology can also be used to directly influence recorders. Existing recorders can be informed where best to record based on current data [ 103 ] (and see also the DECIDE tool in [ 104 ] ). There has also been exploration of the potential to implement chatbots in citizen science projects or on social media.…”
Section: Technology As An Enabler—opening Up New Research Avenuesmentioning
confidence: 99%